Highest Education Smartphones Use and Itâ€™s Relationship with Students Engagement - Fitria, Jihan; Mariono, Andi; Maureen, Irena Yolanita (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
This study aims to explain the influence of smartphones on student engagement in state university students in the city of Surabaya. This study used 85 total samples. This type of research is quantitative research using survey methods with the following stages; observation of research locations, preparation of questionnaires, distribution of questionnaires, validity testing, data collection, processing of research results, analysis of research results, discussion. The results showed that the influence of smartphones on student engagement was 0.057 or 5.7% with a significance of 0.028 <0.05. Test results t-table is greater than t-count, i.e. t-count = 2.232 â‰¥ (t-tab) = 1.989. it can be proven that there is a variable influence of smartphone use on student engagement in state university students in the city of Surabaya. This can be proven from the results of the t test, namely t count 2.232 greater than table 1.989 with a significance level of 0.028. This means that there is an influence on smartphone use on student engagement. Furthermore, when reviewed from the results of the Model Summary table on the R test square scored a coefficient of determination of 0.057 or 5.7%. This means that the variable smartphone use (X1) has a contributing influence on student engagement (Y) by 5.7% and the other 94.3% is influenced by other variables outside the variable of smartphone use.